PELAKSANAAN PERLINDUNGAN HUKUM PEKERJA PADA KAPAL PESIAR YANG DISALURKAN MELALUI PT. WATERFRONT DI DENPASAR - Mas Mahadiani, Sagung Istri; Markeling, I Ketut; Sukranatha, A. A. Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
Employment opportunities abroad are still open with adequate wages, thisreality has become a main attraction for Indonesian workers to seek employmentabroad. Thus the placement of Indonesian workers to work abroad is an attempt torealize the equal rights and opportunities for workers to get a job and a decent incomein the implementation should be done with attention to the dignity, human dignity andthe protection of the law. Indonesian workers to be placed overseas go through the ofthe placement company of Indonesian workers As a distributor overseas executiveplacement must be able to perform the placement and protection for workers who aredistributed in accordance with the applicable provisions.
Keywords: protections, company, employment, overseas